1934
DOI: 10.1017/s0021859600007048
|View full text |Cite
|
Sign up to set email alerts
|

A chemical study of sugar beet during the first growth year

Abstract: 1. An account has been given of the composition and weights of nutrients and sugars in sixty-four sugar beet plants from just before singling until maturity. The assimilation, translocation and distribution of these have been discussed.2. At about singling, the leaves contained 90 per cent. of the dry matter and 76 per cent. of the sugars of the plant, whereas, at maturity, the figures were 28 and 3 per cent. respectively.3. The percentage of reducing sugars in the dry substance of the complete plant maintaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1936
1936
1960
1960

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The loss of phosphorus from the N 2 P plants which did not occur with other treatments, and the entire absence of loss of elements from the N 2 PK plants, are outstanding features of the table. In previous work on wheat (Knowles & Watkin, 1931) and sugar beet (Knowles et al 1934) we have noted losses; in the former plant of potassium, calcium and chlorine, and in the latter of phosphorus and chlorine. Although in the case of wheat our work was concerned only with the aerial parts of the plant, we recorded the opinion that the losses were so large that they were not due to mechanical causes, but to a return of elements to the roots; the losses from beet were suggestive of excretion from roots to the soil.…”
Section: Losses Of Elements Observedmentioning
confidence: 76%
“…The loss of phosphorus from the N 2 P plants which did not occur with other treatments, and the entire absence of loss of elements from the N 2 PK plants, are outstanding features of the table. In previous work on wheat (Knowles & Watkin, 1931) and sugar beet (Knowles et al 1934) we have noted losses; in the former plant of potassium, calcium and chlorine, and in the latter of phosphorus and chlorine. Although in the case of wheat our work was concerned only with the aerial parts of the plant, we recorded the opinion that the losses were so large that they were not due to mechanical causes, but to a return of elements to the roots; the losses from beet were suggestive of excretion from roots to the soil.…”
Section: Losses Of Elements Observedmentioning
confidence: 76%
“…Sugar beet is a crop with a long growing season, and Knowles, Watkin & Hendry (1934) showed that nitrogen uptake was highest in July. To see whether the crop is nitrogen-deficient at the end of June when nitrogen had been leached during a wet spring, the experiments also tested a top dressing at the end of June.…”
mentioning
confidence: 99%
“…As has been noted, it was impractical. to obtain green weights generally; hence the data showing the changes with age in the mineral composition of the plant are expressed upon the dry weight basis 7. It will be recognized that the effect of "age" actually includes the combined effects of age and season.…”
mentioning
confidence: 99%